Using technology to scale-up training and supervision of community health workers in the psychosocial management of perinatal depression: a non-inferiority, randomized controlled trial. (2019) - Rahman, Atif; Akhtar, Parveen; Hamdani, Syed Usman; Atif, Najia; Nazir, Huma; Uddin, Iftikhar; Nisar, Anum; Huma, Zille; Maselko, Joanna; Sikander, Siham; Zafar, Shamsa
Abstract : Background: The Thinking Healthy Programme (THP) is an evidence-based psychological intervention endorsed by the World Health Organization, tailored for non-specialist health workers in low- and middle-income countries. However, training and supervision of large numbers of health workers is a major challenge for the scale-up of THP. We developed a 'Technology-Assisted Cascaded Training and Supervision system' (TACTS) for THP consisting of a training application and cascaded supervision delivered from a distance. Methods: A single-blind, non-inferiority, randomized controlled trial was conducted in District Swat, a post-conflict area of North Pakistan. Eighty community health workers (called Lady Health Workers or LHWs) were randomly assigned to either TACTS or conventional face-to-face training and supervision by a specialist. Competence of LHWs in delivering THP post-training was assessed by independent observers rating a therapeutic session using a standardized measure, the 'Enhancing Assessment of Common Therapeutic factors' (ENACT), immediately post-training and after 3 months. ENACT uses a Likert scale to score an observed interaction on 18 dimensions, with a total score of 54, and a higher score indicating greater competence. Results: Results indicated no significant differences between health workers trained using TACTS and supervised from distance v. those trained and supervised by a specialist face-to-face ( mean ENACT score M = 24.97, s.d. = 5.95 v . M = 27.27, s.d. = 5.60, p = 0.079, 95% CI 4.87–0.27) and at 3 months follow-up assessment ( M = 44.48, s.d. = 3.97 v . M = 43.63, s.d. = 6.34, p = 0.53, CI −1.88 to 3.59). Conclusions: TACTS can provide a promising tool for training and supervision of front-line workers in areas where there is a shortage of specialist trainers and supervisors.